Organizational flow chart of home care for children with special health care needs - Vanessa Rossetto; Beatriz Rosana Gonçalves de Oliveira Toso; Rosa Maria Rodrigues (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To develop a workflow protocol for Home Care (HC) services in the HC2 modality for children with special health care needs (CSHCN) in the state of Parana. Method: Quantitative, descriptive, exploratory, multiple case studies. Data was collected with professionals from the eight home care services in Parana. Data were analyzed using the Strengths, Weaknesses, Opportunities and Threats (SWOT) methodology, from which a 5W2H method of action plan was developed, resulting in a flow chart. Results: Considering the strategies found in Home Care services, such as planned hospital discharge, caregiver training, organized transportation and singular therapeutic project, a flow organization protocol for children with special health care needs in Home Care services was developed. Conclusion: The protocol developed makes it possible to organize the care provided to children with special health care needs in home care.